Lithium Clinics in Berlin and Dresden: a 50-Year Experience - Felber, Werner; Bauer, Michael; Lewitzka, Ute; Müller-Oerlinghausen, Bruno (Pharmacopsychiatry, 2018)
Although lithium’s serendipitous discovery as a medication for depression dates back more than 200 years, the first scientific evidence that it prevents mania and depression arose only in the 1960s. However, at that time there was a lack of knowledge about how to administer and monitor lithium therapy safely and properly. The lithium clinics in Dresden and Berlin were remarkably similar in their beginnings in the late 1960s regarding patient numbers and scientific expertise without being aware of one another due to the Iron Curtain separating Germany into a western and eastern part until 1990. In what were initially lithium-care programs run independently from one another, the lithium clinics embedded in academic settings in Dresden and Berlin represent a milestone in the history of psychopharmacological treatment of affective disorders in Germany and trailblazers for today’s lithium therapy. Nowadays, lithium’s clinical applications are unquestioned, such as its use in strategies to prevent mood episodes and suicide, and to treat depression. The extensively documented knowledge of lithium treatment is the fruit of more than 50 years of observing disease courses and of studying side effects and influencing factors of lithium prophylaxis. Its safe and proper administration—in determining the correct indication, baseline and follow-up examinations, recommended dosages, monitoring, or the management of side effects—is well established. Subsequently, both national and international guidelines continue recommending lithium as the gold standard in treating patients with unipolar and bipolar disorders.
Keywords: lithium; history of lithium care; lithium clinics; affective disorder; prevention of suicide